Systemic Risk : A New Trade-off for Monetary Policy? - Laseen, Stefan (IMF Working Papers; Working Paper ;, 2015)
We introduce time-varying systemic risk in an otherwise standard New-Keynesian model to study whether a simple leaning-against-the-wind policy can reduce systemic risk and improve welfare. We find that an unexpected increase in policy rates reduces output, inflation, and asset prices without fundamentally mitigating financial risks. We also find that while a systematic monetary policy reaction can improve welfare, it is too simplistic: (1) it is highly sensitive to parameters of the model and (2) is detrimental in the presence of falling asset prices. Macroprudential policy, similar to a countercyclical capital requirement, is more robust and leads to higher welfare gains.